2017
DOI: 10.1051/0004-6361/201731129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stellar flares on the upper atmospheres of HD 189733b and HD 209458b

Abstract: Stellar flares are a frequent occurrence on young low-mass stars around which many detected exoplanets orbit. Flares are energetic, impulsive events, and their impact on exoplanetary atmospheres needs to be taken into account when interpreting transit observations. We have developed a model to describe the upper atmosphere of Extrasolar Giant Planets (EGPs) orbiting flaring stars. The model simulates thermal escape from the upper atmospheres of close-in EGPs. Ionisation by solar radiation and electron impact i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 72 publications
(109 reference statements)
2
28
0
Order By: Relevance
“…Atmospheric escape has been observed on a handful of hot Jupiters to date, namely HD209458b, HD189733b, and WASP-12b (Vidal-Madjar et al 2003;Lecavelier des Etangs et al 2010, 2012Fossati et al 2010). Models of more moderately irradiated hot Jupiters HD209458b and HD189733b indicate that atmospheric escape does not drastically alter the total mass of these planets throughout the planet's lifetime (e.g., Yelle 2004Yelle , 2006Murray-Clay et al 2009;Koskinen et al 2013;Chadney et al 2017). The same does not necessarily hold for extreme hot Jupiters such as WASP-12b that undergo significant Roche lobe overflow in addition to thermal escape due to their close orbit around the host star (Li et al 2010;Jackson et al 2017).…”
Section: The Upper Atmosphere and Atmospheric Escape On Hot Jupitersmentioning
confidence: 99%
“…Atmospheric escape has been observed on a handful of hot Jupiters to date, namely HD209458b, HD189733b, and WASP-12b (Vidal-Madjar et al 2003;Lecavelier des Etangs et al 2010, 2012Fossati et al 2010). Models of more moderately irradiated hot Jupiters HD209458b and HD189733b indicate that atmospheric escape does not drastically alter the total mass of these planets throughout the planet's lifetime (e.g., Yelle 2004Yelle , 2006Murray-Clay et al 2009;Koskinen et al 2013;Chadney et al 2017). The same does not necessarily hold for extreme hot Jupiters such as WASP-12b that undergo significant Roche lobe overflow in addition to thermal escape due to their close orbit around the host star (Li et al 2010;Jackson et al 2017).…”
Section: The Upper Atmosphere and Atmospheric Escape On Hot Jupitersmentioning
confidence: 99%
“…Lecavelier Des Etangs et al (2010) estimate the current mass loss rate to be in the range of 10 9 and 10 11 gs −1 . Other estimates for the mass loss have been made such as the model by Chadney et al (2017), who calculate an upper limit to the mass loss rate of HD 189733b of the order of 10 7 and 10 12 gs −1 during stellar flares with large scale proton events. Our calculation, based on the energy-limited escape model, estimates a current mass loss rate of about 1.8×10 11 gs −1 , which is at the upper end, but compatible with the estimates based on hydrogen Ly-α observations.…”
Section: Exoplanet Mass Loss Rates In Contextmentioning
confidence: 99%
“…If the mass-loss efficiency for flares is similar to the canonical value of 0.1 for steadystate flux (e.g., Murray-Clay et al 2009), then the accumulated atmospheric "erosion" by such flares could be significant over timescales of hundreds of Myr. Chadney et al (2017) modeled the effects of a flare on mass loss from hot Jupiters and found that it could not explain variations seen in the Lyα transit of HD 189733b. More modeling is needed to determine the efficiency of flare EUV emission in removing atmospheric mass over a range of planetary parameters (e.g.…”
Section: Planetary Implications Of the Hazflarementioning
confidence: 99%